Identifikasi Potensi Pariwisata di Kabupaten Sukabumi: Identification of Tourism Poteneial in Regency of Sukabumi - Nurul Syifa Novita Adela Choirunisa (Jurnal Agribisnis dan Pembangunan Pertanian (JAPP), 2023)
Sukabumi Regency offered a very charming natural that attracted the eyes of tourists. Due to Sukabumi District's vast natural resources, local people recognised the term GURILAPS which stands for Mountain, Jungle, Sea, Beach and River. In addition, there are many popular natural resource-based tourism sites in Sukabumi District, especially Region 7 which consists of several sub-districts; Pabuaran, Sagaranten, Curug Kembar, Cidadap, Tegal Buled, and Cidolog which can be potential as tourism sites. However, these abundant natural resources have not been fully managed. Therefore, this study was conducted to determine the tourism potential of Sukabumi District. The method used was descriptive analysis. The results of the identification can be concluded that Sukabumi Regency has abundant resources, both natural and socio-cultural resources that can be used as tourism and have the potential to be developed.